NEW INTEGRAL INEQUALITIES FOR PREINVEX FUNCTIONS VIA CAPUTO FRACTIONAL DERIVATIVES - Meftah, Badreddine; Kashuri, Artion (Matematichki Bilten, 2021)
Abstract. In this paper we present the analogue of Hermite-Hadamard inequality for preinvex functions via Caputo fractional derivatives. Moreover, we establish a new integral identity and derive some new trapezium type inequalities for preinvex functions via Caputo fractional derivatives.